Immunopathology of Airway Surface Liquid Dehydration Disease - Brandon W. Lewis; Sonika Patial; Yogesh Saini (Journal of Immunology Research)
The primary purpose of pulmonary ventilation is to supply oxygen (O2) for sustained aerobic respiration in multicellular organisms. However, a plethora of abiotic insults and airborne pathogens present in the environment are occasionally introduced into the airspaces during inhalation, which could be detrimental to the structural integrity and functioning of the respiratory system. Multiple layers of host defense act in concert to eliminate unwanted constituents from the airspaces. In particular, the mucociliary escalator provides an effective mechanism for the continuous removal of inhaled insults including pathogens. Defects in the functioning of the mucociliary escalator compromise the mucociliary clearance (MCC) of inhaled pathogens, which favors microbial lung infection. Defective MCC is often associated with airway mucoobstruction, increased occurrence of respiratory infections, and progressive decrease in lung function in mucoobstructive lung diseases including cystic fibrosis (CF). In this disease, a mutation in the cystic fibrosis transmembrane conductance regulator (CFTR) gene results in dehydration of the airway surface liquid (ASL) layer. Several mice models of Cftr mutation have been developed; however, none of these models recapitulate human CF-like mucoobstructive lung disease. As an alternative, the Scnn1b transgenic (Scnn1b-Tg+) mouse model overexpressing a transgene encoding sodium channel nonvoltage-gated 1, beta subunit (Scnn1b) in airway club cells is available. The Scnn1b-Tg+ mouse model exhibits airway surface liquid (ASL) dehydration, impaired MCC, increased mucus production, and early spontaneous pulmonary bacterial infections. High morbidity and mortality among mucoobstructive disease patients, high economic and health burden, and lack of scientific understanding of the progression of mucoobstruction warrants in-depth investigation of the cause of mucoobstruction in mucoobstructive disease models. In this review, we will summarize published literature on the Scnn1b-Tg+ mouse and analyze various unanswered questions on the initiation and progression of mucobstruction and bacterial infections.